New insights on neurodegeneration triggered by iron accumulation: Intersections with neutral lipid metabolism, ferroptosis, and motor impairment - Maniscalchi Velásquez, Athina del Valle (2024)
Brain iron accumulation constitutes a pathognomonic indicator in several neurodegenerative disorders. Metal accumulation associated with dopaminergic neuronal death has been documented in Parkinson's disease. Through the use of in vivo and in vitro models, we demonstrated that lipid dysregulation manifests as a neuronal and glial response during iron overload. In this study, we show that cholesterol content and triacylglycerol (TAG) hydrolysis were strongly elevated in mice midbrain. Lipid cacostasis was concomitant with the loss of dopaminergic neurons, astrogliosis and elevated expression of α-synuclein. Exacerbated lipid peroxidation and markers of ferroptosis were evident in the midbrain from mice challenged with iron overload. An imbalance in the activity of lipolytic and acylation enzymes was identified, favoring neutral lipid hydrolysis, and consequently reducing TAG and cholesteryl ester levels. Notably, these observed alterations were accompanied by motor impairment in iron-treated mice. In addition, neuronal and glial cultures along with their secretomes were used to gain further insight into the mechanism underlying TAG hydrolysis and cholesterol accumulation as cellular responses to iron accumulation. We demonstrated that TAG hydrolysis in neurons is triggered by astrocyte secretomes. Moreover, we found that the ferroptosis inhibitor, ferrostatin-1, effectively prevents cholesterol accumulation both in neurons and astrocytes. Taken together, these results indicate that lipid disturbances occur in iron-overloaded mice as a consequence of iron-induced oxidative stress and depend on neuron-glia crosstalk. Our findings suggest that developing therapies aimed at restoring lipid homeostasis may lead to specific treatment for neurodegeneration associated with ferroptosis and brain iron accumulation.